2022
DOI: 10.1177/23996544221148032
|View full text |Cite
|
Sign up to set email alerts
|

“I choose fish”: Understanding informal civil society in Vietnam through environmental grievances and actions

Abstract: This paper focuses on informal civil society in an authoritarian context, particularly the unprecedented nation-wide protests and civic action in Vietnam, triggered by the industrial pollution and the resulting mass fish death on the central coast in 2016. We explore civil society actors' motivations and tactics to take action under political restrictions. Data was collected from semi-structured interviews with civil society actors. The findings illustrate how informal civil society in Vietnam is built on inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…The use of social media, particularly Facebook, to assign a variety of problem-making claims about the disaster allowed the development of a connection action network that was far more individualised and technologically organised than traditional collective actions networks (Bennett and Segerberg, 2012). The #ichoosefish was associated with different interpretations of the grievances, and allowed a variety of Facebook and Twitters users to form perception of and attachment to the marine disaster and its many consequences (Nguyen Van Quoc and Trell, 2020). The abstractness of environmentalism or anti-Chinaism thus became personalised, rendering a broader population of users acceptive to mobilisation.[…] ‘environment’ is too generic and broad, so a specific narrative would be easier to attract attention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of social media, particularly Facebook, to assign a variety of problem-making claims about the disaster allowed the development of a connection action network that was far more individualised and technologically organised than traditional collective actions networks (Bennett and Segerberg, 2012). The #ichoosefish was associated with different interpretations of the grievances, and allowed a variety of Facebook and Twitters users to form perception of and attachment to the marine disaster and its many consequences (Nguyen Van Quoc and Trell, 2020). The abstractness of environmentalism or anti-Chinaism thus became personalised, rendering a broader population of users acceptive to mobilisation.[…] ‘environment’ is too generic and broad, so a specific narrative would be easier to attract attention.…”
Section: Resultsmentioning
confidence: 99%
“…We also look into the on-going struggles along the Mekong River, exemplified by the severe drought in 2016, which received considerable attention at policy levels yet little from the bottom-up. Our previous analysis found that despite their silence due to the political sensitivity, institutionalised actors did attempt to get involved and assert influence on the marine disaster (Nguyen Van Quoc & Trell, 2020). This prompted the question of the relationship between environmental politicisation and the corresponding public reaction, particularly from the communities at risk and the activists involved.…”
Section: Introductionmentioning
confidence: 99%